SOCIO-COMMUNICATIONAL INFORMAL INTERACTIONS WITHIN THE SOCIAL REINTEGRATION STAFF IN A ROMANIAN DETENTION UNIT. ROLE MODEL CASE STUDY - Laurentiu-Octavian Mutuleanu (Social Sciences and Education Research Review)
The findings from the study on socio-communicational interactions on informal topics among the social reintegration staff of a Romanian detention unit, using sociometry and organizational network analysis (ONA), have been further explored in this article. The first objective is to investigate the association between the highest values of the "subjective reflection of employees' perception regarding colleagues' knowledge about mobile phones" indicator and the "role model" indicator obtained by group members. The second objective is to investigate the association between the highest values of the "role model" indicator obtained by group members and the "employees' influence power" indicator. This research is useful for decision-makers in prisons because it shows new ways (related to the first study) to discover key opinion informal leaders, that individuals who benefit from increased social capital, which in fact represents sustainable human resources for organizational leadership. Such employees can contribute to the generation and facilitation of knowledge transfer or information flow within the network, including promoting the adoption of new management policies, increasing the cohesion degree within the group and providing operational and emotional support to colleagues. The sources of the research are books and articles that develop the subject of social network analysis, some of which are written by well-known authors. In order to achieve proposed objectives, it was necessary to discover the employees' informal socio-communicational networks, both the social support network and the trust network, within the social reintegration sector, which represent the target group. The networks were identified by administering a questionnaire to the members of the social reintegration sector. The purpose of the questionnaire was to obtain and illustrate the relationship choices (connections) expressed by each employee in the context of informal social interactions on topics unrelated to work. The questionnaire was administered digitally through the Google Forms platform with the agreement of the participants, after obtaining approval from the institution's management. After depicting the employees' informal networks, specific centrality measurements were applied using sociometry and ONA research methods to identify the values of the "role model" indicator, "power of influence" (Eigenvector-Authority In) indicator and the employees' "subjective reflected perception" indicator (members of the target group). The quantifiable values of the indicators were obtained by applying statistical calculation procedures specific to sociometry and ONA, using both Microsoft Excel and IBM i2 Analyst's Notebook software. After testing hypotheses in the context of discussions about leisure activities, the following conclusions were drawn regarding individuals who benefit from increased social capital, respectively those who occupy the most important positions on the "role model" status value scale related to knowledge of mobile phones